PENGARUH TERAPI MUSIK KLASIK TERHADAP PENURUNAN TINGKAT KECEMASAN PADA IBU PRE OPERASI SECTIO CAESAREA - emilda emilda (JURNAL KESEHATAN INDRA HUSADA, 2021)
Background : Sectio caesarea surgery has complications of infection, bleeding, bladder injury, pulmonary embolism, uterine rupture, and perinatal fetal death, which can cause concern and anxiety. Relaxation therapy is an alternative that can be given to reduce the anxiety response. Music has been shown to control neurophysiological levels that can create a relaxing effect through central and autonomic nervous responses. Objectives : To determine the effect of classical music therapy on reducing anxiety levels in mothers per sectio caesarea operation at Langsa City Hospital. Methods : The research design used in this study is a quasi-experimental experiment, which is an experiment that does not or does not have the characteristics of an actual experimental design. The approach chosen is One Group Pre Test – Post Test Design, namely research that uses one group of subjects, measurements are taken before being given the intervention and after being given the intervention. The number of samples in the study were 21 people obtained by Accidental Sampling. Results : The results of statistical tests obtained P value = 0.000, which means P value < (0.000 < 0.05), it can be concluded that there is an effect of giving music therapy to decrease anxiety levels in preoperative sectio caesarea mothers. Conclusion: Classical music therapy can reduce anxiety levels in preoperative sectio caesarea mothers.